2006
DOI: 10.1007/s00249-006-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally resolved time-correlated single photon counting: a novel approach for characterization of endogenous fluorescence in isolated cardiac myocytes

Abstract: A new setup for time-resolved fluorescence micro-spectroscopy of cells, based on multi-dimensional time-correlated single photon counting, was designed and tested. Here we demonstrate that the spectrometer allows fast and reproducible measurements of endogenous flavin fluorescence measured directly in living cardiac cells after excitation with visible picosecond laser diodes. Two complementary approaches for the analysis of spectrally- and time-resolved autofluorescence data are presented, comprising the fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 23 publications
2
72
0
Order By: Relevance
“…Data were analyzed using SPCImage software (Becker&Hickl, Boston Electronics, U.S.A), as described previously [8,12]. Data are shown as mean AE standard error (SEM).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Data were analyzed using SPCImage software (Becker&Hickl, Boston Electronics, U.S.A), as described previously [8,12]. Data are shown as mean AE standard error (SEM).…”
Section: Discussionmentioning
confidence: 99%
“…Our previously obtained data in rat cardiomyocytes [6][7][8] clearly showed that metabolic state can be determined directly in living cardiac cells by monitoring their naturally occurring endogenous AF. Such AF, generated after excitation with UV or visible light is localized in mitochondria and is mainly resulting from mitochondrial oxidized flavins (FAD * ) and reduced NAD(P)H [9], principal endogenous indicators of cellular oxidative metabolism.…”
Section: Biophotonicsmentioning
confidence: 95%
See 2 more Smart Citations
“…7,12 Picosecond laser diode BDL-375 (Becker&Hickl, Boston Electronics, USA) with emission at 375 nm was deployed at the 20 MHz repetition rate as an excitation source. All experiments were performed at room temperature.…”
Section: Time-resolved Spectroscopy Measurements Of Nad(p)h Fluorescencementioning
confidence: 99%